Steroid constituents from Lobophytum crassum - Thao, Nguyen Phuong; Thanh, Nguyen Van; Nam, Nguyen Hoai; Cuong, Nguyen Xuan; Kim, Young Ho; Kiem, Phan Van; Minh, Chau Van (Vietnam Journal of Chemistry, 2015)
Using various chromatographic methods, three sterols, (22R,23R,24R)-5α,8α-epidioxy-22,23-methylene-24-methylcholest-6-ene-3β-ol (1), ergosterol peroxide (2), and 3β-hydroxyandrost-5-ene-17-one (3), were isolated from the methanol extract of the soft coral Lobophytum crassum. Their structures were elucidated by 1D and 2D-NMR experiments and comparison of their NMR data with reported values. Compounds 1-3 were isolated from L. crassum for the first time.